On Investigation of the convergence by least square method for solving Fredholm integral - Mohammad Hasso; Aml Mohammed (College of Education for Pure Sciences, 2008)
Abstract In this paper we used the improved least square method presented to solve Fredholm integral equation of the second kind .This method combines, forward and backward factorial polynomial and quasi orthogonal polynomial. These polynomials improved the above method and getting it to a strong convergence property .The numerical results are agreeable in comparison with exact solution .